Deficient brain insulin signalling pathway in Alzheimer’s disease and diabetes - Liu, Ying (J Pathol, 2011)
Brain glucose metabolism is impaired in Alzheimer’s disease (AD), the most common form of dementia. Type 2 diabetes mellitus (T2DM) is reported to increase the risk for dementia, including AD, but the underlying mechanism is not understood. Here, we investigated the brain insulin–PI3K–AKT signalling pathway in the autopsied frontal cortices from nine AD, 10 T2DM, eight T2DM–AD and seven control cases. We found decreases in the levels and activities of several components of the insulin–PI3K–AKT signalling pathway in AD and T2DM cases. The deficiency of insulin–PI3K–AKT signalling was more severe in individuals with both T2DM and AD (T2DM–AD). This decrease in insulin–PI3K–AKT signalling could lead to activation of glycogen synthase kinase-3β, the major tau kinase. The levels and the activation of the insulin–PI3K–AKT signalling components correlated negatively with the level of tau phosphorylation and positively with protein O-GlcNAcylation, suggesting that impaired insulin–PI3K–AKT signalling might contribute to neurodegeneration in AD through down-regulation of O-GlcNAcylation and the consequent promotion of abnormal tau hyperphosphorylation and neurodegeneration. The decrease in brain insulin–PI3K–AKT signalling also correlated with the activation of calpain I in the brain, suggesting that the decrease might be caused by calpain over-activation. Our findings provide novel insight into the molecular mechanism by which type 2 diabetes mellitus increases the risk for developing cognitive impairment and dementia in Alzheimer’s disease.